Recent evolution of poverty in the European countries - Juana Domínguez-Domínguez; José Javier Nú\~nez-Velázques; Luis Felipe Rivera-Galicia (European Regional Science Association (ERSA), 2004)
The purpose of this paper is to analyze the evolution of poverty in the 15 countries of E.U., whose household income data is available through the information contained in the European Community Household Panel (ECHP). Several indicators have been proposed in economic literature for measuring poverty, but they may produce different orderings when cases are compared. In this work, a set of poverty one-dimensional indicators are chosen, which best verify some desirable properties. A modification of the Principal Component Analysis (PCA) is proposed to calculate synthetic cross-sectional measures of poverty using this set of indicators. In order to obtain comparable values throughout time, in addition to cross-sectional sense, joint consideration of single poverty indicators is proposed, independently of their temporary period of reference. Therefore, applying common space analysis to these cross-sectional synthetic measures, a common frame of comparison and a homogeneous weighting structure are obtained, which are stable throughout time. This powerful tool allows static as well as dynamic comparisons, among the EU countries. Furthermore, the determination of groups of countries according to their characteristics in poverty will be accomplished.
Keywords: 330